2014
DOI: 10.1177/0003122414545986
|View full text |Cite
|
Sign up to set email alerts
|

The Parity Penalty in Life Course Perspective

Abstract: Research documents a wage penalty for mothers compared to childless women. We demonstrate there is also an occupational status penalty to motherhood. Interrogating supply- and demand-side explanations of the motherhood penalty from the life course perspective, we formulate and test original hypotheses about the short-term and long-run career implications of parity-specific births. We analyze longitudinal data from the European Community and Household Panel for 13 European countries and eight time points betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(48 citation statements)
references
References 57 publications
(148 reference statements)
1
46
0
1
Order By: Relevance
“…In fact, a second child or third child hardly seems to affect women's earnings at all. Adjustments to women's employment therefore indeed seem to be most drastic following the birth of first child (Abendroth et al, 2014). Our findings are also in line with data from Statistics Netherlands (Bierings & Souren, 2011), which showed that working hours are most strongly affected by the birth of a first child.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In fact, a second child or third child hardly seems to affect women's earnings at all. Adjustments to women's employment therefore indeed seem to be most drastic following the birth of first child (Abendroth et al, 2014). Our findings are also in line with data from Statistics Netherlands (Bierings & Souren, 2011), which showed that working hours are most strongly affected by the birth of a first child.…”
Section: Discussionsupporting
confidence: 90%
“…We question this assumption, arguing that the reduction in income after a second or third child is less pronounced, as major adjustments to employment mostly take place following the birth of the first child. A recent study on occupational attainment following motherhood is in line with the notion that the transition to motherhood is the crucial factor, not the arrival of subsequent children (Abendroth, Huffman, & Treas, 2014).…”
mentioning
confidence: 55%
See 3 more Smart Citations